Perlindungan Khusus Bagi Anak Penyandang Disabilitas di Kota Padang - Kurnia Putri, Windi; Eka Putri, Nora (PUBLICNESS: Journal of Public Administration Studies, 2024)
In Padang City, the number of children with disabilities continues to rise each year. Although the state guarantees their protection, these children still face significant challenges, such as violence, unmet rights, and persistent stigma and discrimination. This study employs a qualitative descriptive method, with informants selected through purposive sampling and data analysis conducted through reduction, presentation, and conclusion drawing. The research reveals that special protection for children with disabilities remains suboptimal. This is evident in the unfulfilled policy implementation indicators proposed by George C. Edward III, which include communication, resources, disposition, and bureaucratic structure. Issues include limited community outreach, insufficient specialized human resources for handling children with disabilities, and inadequate infrastructure supporting accessibility. Therefore, improvements in policy implementation strategies and increased public awareness are necessary to create an inclusive environment for children with disabilities.